2011
DOI: 10.1007/s11199-011-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Invisible or Involved Fathers? A Content Analysis of Representations of Parenting in Young Children’s Picturebooks in the UK

Abstract: Although gender-role stereotyping in children's books is a consistent focus of research, the study of the gender role stereotyping of parenting in particular is less common, despite a developing academic interest in the changing social meanings of fathering and mothering in contemporary societies. Previous analysis has suggested that fathers are under-represented in children's books and when present, are less likely than mothers to be featured expressing affection towards, or caring for, children. This paper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
(63 reference statements)
2
26
0
Order By: Relevance
“…Absentee fathers have been noted in other studies of information documents. For example, studies focused on children's picture books found that fathers were invisible or emotionally unavailable in many depictions of family dynamics (Adams, et al, 2011;Anderson & Hamilton, 2005). Excluding fathers from parenting literature and information documents perpetuates notions that mothers are and should be the primaryand at times, the solecaregivers, and that fathers do not need to educate themselves about children and their care.…”
Section: Resultsmentioning
confidence: 99%
“…Absentee fathers have been noted in other studies of information documents. For example, studies focused on children's picture books found that fathers were invisible or emotionally unavailable in many depictions of family dynamics (Adams, et al, 2011;Anderson & Hamilton, 2005). Excluding fathers from parenting literature and information documents perpetuates notions that mothers are and should be the primaryand at times, the solecaregivers, and that fathers do not need to educate themselves about children and their care.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, children's media can provide important messages about identity (Ayres, 2004;Janson, 2012;Jung & Peterson, 2007;Parlevliet, 2011). Yet, this invisibility is consequential, as it can influence attitudes toward the value of certain family members (Adams et al, 2011) or family types (Rodman & Hildreth, 2002). Yet, relatively little attention has been paid to sibling experiences or portrayals.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rodman and Hildreth (2002), the general publishing market does not provide easy or mass market access to diverse family literature. Given that stories can have significant consequences for identity (e.g., Adams et al, 2011), this would seem to be a valuable skill that family and consumer science practitioners can provide. Fourth, practitioners can teach families strategies for evaluating the social messages in their media use.…”
Section: Recommendations For Practitioners/service Providersmentioning
confidence: 99%
See 2 more Smart Citations